1985
DOI: 10.1111/j.1365-2125.1985.tb02793.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of captopril on the reflex control heart rate: possible mechanisms.

Abstract: 1 Angiotensin converting enzyme inhibitors reduce blood pressure without reflex tachycardia, possibly as a result of enhanced hypothesis that this results from the removal of the parasympathetic activity. We examined the vagolytic action of angiotensin II or alternatively by acetylcholinesterase inhibition.2 Both captopril and [Sar1ala8] angiotensin II, (saralasin), caused modest falls in blood pressure, without increasing heart rate in normotensive subjects. 3 Captopril and saralasin significantly attenuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…21 They also show lack of reflex tachycardia 22 and cause inhibition of the normal tonic influence of Ang II on the sympathetic nervous system. 23 During ACE inhibition, heart rate responses to postural changes and exercise are not impaired. 24 …”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 99%
“…21 They also show lack of reflex tachycardia 22 and cause inhibition of the normal tonic influence of Ang II on the sympathetic nervous system. 23 During ACE inhibition, heart rate responses to postural changes and exercise are not impaired. 24 …”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 99%
“…The absence of reflex tachycardia with blood pressure reduction after ACE inhibitors appears, in part, to be related to an enhancement of cardiac parasympathetic tone (Sturani et al, 1982;Campbell et al, 1985;Ajayi et al, 1985a) following the withdrawal of the vagolytic actions of angiotensin II (Ajayi et al, 1985b).…”
Section: Autonomic Function Testsmentioning
confidence: 99%
“…The absence of reflex cardioacceleration, even after acute dosing, suggests that ACE inhibitors exert some specific influence on, for example, autonomic reflex mechanisms or baroreflex integrity. There is no evidence to suggest that ACE inhibition significantly modifies either sympathetic tone or baroreflex function in man (Millar et al, 1982) but enhancement of-cardiac parasympathetic activity has been reported with captopril, enalapril and lisinopril (Sturani et al, 1982;Campbell et al, 1985;Ajayi et al, 1985a, b …”
Section: Introductionmentioning
confidence: 99%